NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR’AN SURAT ALI IMRAN AYAT 37 - Chumaidah Syc; Yuni Astutik (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
Abstract: Islamic education is an important part in the world of education. Because humans not only need knowledge, but also need spiritual power of religion to form a whole human being (insan kamil) in accordance with Islamic norms. This study discusses